Evaluating anti-poverty programs - Ravallion, Martin, 1952- 1952- (Policy research working paper, 2005)
"The author critically reviews the methods available for the ex-post counterfactual analysis of programs that are assigned exclusively to individuals, households, or locations. The discussion covers both experimental and non-experimental methods (including propensity-score matching, discontinuity designs, double and triple differences, and instrumental variables). Two main lessons emerge. First, despite the claims of advocates, no single method dominates; rigorous, policy-relevant evaluations should be open-minded about methodology. Second, future efforts to draw more useful lessons from evaluations will call for more policy-relevant measures and deeper explanations of measured impacts than are possible from the classic ("black box") assessment of mean impact. "--World Bank web site